Globalizing Local Content as A New Concept In Planning Education: Experience in Developing Double Master Degree Program Between University of Groningen, The Netherlands and Institut Teknologi Bandung, Indonesia - Winarso, Haryo (Journal of Regional and City Planning, 2007)
In  the past, developing  curricula  for  planning  education  in  developing countries  could  mean  asking  for  assistance  from  the  western universities to set up a degree program, using western planning tools to be  put  into  social  and  cultural  specific  of  the  developing  countries. Most  of  such  collaboration  would  ignore  the  potency  of  knowing  the two  different  worlds.  Those  view  is  no  longer   appropriate  as globalisation  in  planning  discipline  is  inescapable,  dualistic  views  on the planning in rich and poor countries has to be seen as a strong point for  planning  education  especially  because  education  itself   is  now globalising.  The  trend  for  global  education  is  visible,  collaboration between  developed  and  developing  countries  universities  are everywhere  not  only  for  the  financial  reasons  but  also  because economic, environment, social and cultural development are now cross border,  and  this  often  involving  conflict  and  a lliance  across  ethno national.  Within  the  above framework,  this  paper  discusses  the development  of  curricula  of  the  Department  of  City  and  Regional Planning of the Institute Teknologi Bandung, since the department was set  up with  the  help  of  the  United  Nation  in  1959;  the  development  of  Master  degree  programme  with  the  assistance  of  the  DevelopmentPlanning  Unit,  University  College  London;  and  the  development  of Double Master Degree Programme in collaboration with the Faculty of Spatial  Sciences,  RUG.  It  is  argued  that  the  curricula  has  been developed in  response to the  changing planning  context in national as well as international level and that planning education has to be able to enrich  students  not  only  with  the  analytical,  tech nical  and  socio political knowledge of local content of developing countries but also the content  of  developed  countries  as  these  two  knowledge  will  enhance understanding of global development problems.